Hooked on a feline - Kelly, Sofie, 1958- (Kelly, Sofie, 1958- Magical cats mystery., 2021)
"After a music festival comes to the quiet town of Mayville Heights, librarian Kathleen Paulson and her inquisitive cats find themselves in a jam when a musician turns up dead. It is summer in Mayville Heights, and Kathleen Paulson and her detective boyfriend, Marcus, are eager to attend the closing concert of the local music festival. The concert is a success, although one of the band members is discovered dead shortly after it. At first it is assumed the death is a robbery gone wrong, but Kathleen suspects foul play-and she is certain that she, along with her trusty side-cats, Owen and Hercules, can help solve the murder. Before his death, Kathleen had noticed the victim in the library researching his genealogy, and when she and Marcus take a closer look at the man's family tree, they begin to think a previous death of one of his relatives now seems suspicious. The more Kathleen thinks about it, the more this murder feels like it could be an encore performance. Kathleen and her cats will need to act fast and be very careful if they want to stay off of a killer's hit list"--